Alteration in faecal bile acids, gut microbial composition and diversity after laparoscopic sleeve gastrectomy. Issue 12 (20th May 2020) - Ikeda, T; Aida, M; Yoshida, Y; Matsumoto, S; Tanaka, M; Nakayama, J; Nagao, Y; Nakata, R; Oki, E; Akahoshi, T; Okano, S; Nomura, M; et al.
Abstract: Background: Laparoscopic sleeve gastrectomy (LSG) is a well established treatment for severe obesity and type 2 diabetes. Although the gut microbiota is linked to the efficacy of LSG, the underlying mechanisms remain elusive. The effect of LSG for morbid obesity on the gut microbiota and bile acids was assessed here. Methods: Severely obese subjects who were candidates for LSG were included and followed until 6 months after surgery. The composition and abundance of the microbiota and bile acids in faeces were assessed by 16S ribosomal RNA sequencing, quantitative PCR and liquid chromatography–mass spectrometry. Results: In total, 28 patients with a mean(s.d.) BMI of 44·2(6·6) kg/m 2 were enrolled. These patients had achieved excess weight loss of 53·2(19·0) per cent and showed improvement in metabolic diseases by 6 months after LSG, accompanied by an alteration in the faecal microbial community. The increase in α-diversity and abundance of specific taxa, such as Rikenellaceae and Christensenellaceae, was strongly associated with reduced faecal bile acid levels. These changes had a significant positive association with excess weight loss and metabolic alterations. However, the total number of faecal bacteria was lower in patients before (mean(s.d.) 10·26(0·36) log10 cells per g faeces) and after (10·39(0·29) log10 cells per g faeces) operation than in healthy subjects (10·83(0·27) log10 cells per g faeces). Conclusion: LSG is associated with a reduction in faecal bile acids and greater abundance of specific bacterial taxa and α-diversity that may contribute to the metabolic changes. Graphical Abstract: Obesity is the most common metabolic disease, with an increasing trend worldwide. Bariatric surgery has been proven to be the best line of treatment for morbid obesity. Laparoscopic sleeve gastrectomy (LSG) is a well established treatment for severe obesity and type 2 diabetes. To clarify the mechanisms underlying the efficacy of LSG, this study examined the effect of LSG on the gut microbiota and bile acids (BAs) in patients with morbid obesity. The findings indicated an increase in α-diversity and abundance of specific taxa, such as Rikenellaceae and Christensenellaceae, which was strongly associated with reduced faecal BA levels. These changes were closely associated with excess weight loss and metabolic alterations. However, the total number of bacteria in patients before and after surgery was lower than that in healthy subjects. Quantitative abnormalities in major gut bacteria in patients with morbid obesity were not restored after operation. These findings indicate that LSG alone has limited effects on obesity-related dysbiosis in the gut microbiota. %EWL, percentage excess weight loss; BW, bodyweight; HbA1c, haemoglobin A1c; HOMA-R, homeostasis model assessment ratio; HOMA-β, homeostasis model assessment of β-cell function; CPI, C peptide immunoreactivity index; CPR, C peptide immunoreactivity; ALT, alanine aminotransferase; AST, aspartate aminotransferase; TG, triglyceride; HDL, high-density lipoprotein; PD, phylogenetic diversity; F/B, Firmicutes/Bacteroidetes. Insights into the altered microenvironment